A multi-objective approach for optimizing emergency material locations in natural disasters - Fan, P. (Advances in production engineering and management, 2025)
In response to the increasing frequency of natural disasters globally, and particularly in the Guangxi Zhuang Autonomous Region, this study aims to optimize the site selection for emergency supplies storage facilities. Traditional methods for predicting emergency supplies demand rely heavily on expert judgment, lacking sophisticated forecasting methodologies, which further complicates research due to the inherent unpredictability of natural disasters. This paper adopts a multi-objective programming approach, leveraging historical data and the proposed emergency supplies demand model to systematically address the spatial layout planning problem of emergency material reserve nodes. After comprehensively considering various factors, including risk, economic, and time-related aspects, a 0-1 integer programming model was established, aiming to fulfill all regional requirements for essential resources within minimal rescue timeframes while minimizing overall costs. Through the application of the AHP-Entropy weight method, data standardization and indicator weighting were conducted, resulting in a hierarchical site selection framework that ensures timely emergency response across the region without incurring prohibitive costs. This study represents a significant contribution to the literature by focusing on the unique challenges and requirements of Guangxi and proposing a tailored approach to optimizing the site selection and layout of emergency supplies storage facilities, thereby enhancing disaster preparedness and response strategies effectively.
Keywords: 0-1 integer programming model; analytic hierarchy process; blagovne rezerve; cross-regional distribution; emergency rescue; emergency supplies storage; grade-based location selection system; izbira lokacije zalog materiala; location optimization; multi-objective optimization; naravne nesreče; natural disasters; optimizacija; pravočasen odziv; risk level; upravljanje tveganj; večkriterijska optimizacija